The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bbr.2016.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic expression of inflammatory mediators in an animal model of binge eating

Abstract: Binge eating episodes are characterized by uncontrollable, distressing eating of a large amount of highly palatable food and represent a central feature of bingeing related eating disorders. Research suggests that inflammation plays a role in the onset and maintenance of eating-related maladaptive behavior. Markers of inflammation can be selectively altered in discrete brain regions where they can directly or indirectly regulate food intake. In the present study, we measured expression levels of different comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 60 publications
0
28
1
Order By: Relevance
“…In previous studies we observed that in the estrous phase of the ovarian cycle, female rats do not exhibit binge eating using our model (Alboni et al, 2017;Micioni Di Bonaventura et al, 2017) while in all other three phases, the rats exhibit binge eating without significant differences in intensity. Therefore, to control for the estrous cycle, immediately after the test on d 25, vaginal smears were collected and analyzed under microscope by an experimenter blind to treatment conditions.…”
Section: Experiments 1 Effect Of the Crf1 Receptor Antagonist R1219mentioning
confidence: 49%
See 1 more Smart Citation
“…In previous studies we observed that in the estrous phase of the ovarian cycle, female rats do not exhibit binge eating using our model (Alboni et al, 2017;Micioni Di Bonaventura et al, 2017) while in all other three phases, the rats exhibit binge eating without significant differences in intensity. Therefore, to control for the estrous cycle, immediately after the test on d 25, vaginal smears were collected and analyzed under microscope by an experimenter blind to treatment conditions.…”
Section: Experiments 1 Effect Of the Crf1 Receptor Antagonist R1219mentioning
confidence: 49%
“…This stress procedure has face validity as a model of the putative contributions of dieting and negative-valence states, to binge eating in humans (Association, 2013; Mathes, Brownley, Mo, & Bulik, 2009; Sanislow et al, 2010; Treasure, Claudino, & Zucker, 2010; Vannucci et al, 2015). Considering the high prevalence of binge eating in women (Hudson et al, 2007; Swanson et al, 2011), we used female rats, in which binge-like eating behavior varies across the estrus cycle (Alboni et al, 2017; Micioni Di Bonaventura et al, 2017), similarly to women (Culbert, Racine, & Klump, 2016; Edler, Lipson, & Keel, 2007; Klump et al, 2013; Schoofs, Chen, Braunig, Stamm, & Kruger, 2011) and this result increases the validity of the model that can be used in translational studies of the mechanism of binge eating behavior.…”
mentioning
confidence: 99%
“…On day 25, the final test day, each group was exposed or not to stress (15 min) (see Figure 1 for details). We found in a previous study that stress-induced BE in our model is not observed during the estrous phase (Alboni et al, 2017;Micioni Di Bonaventura, Lutz et al, 2017). In these conditions, the animal was able to see the cup and the palatable food itself and could smell its odor.…”
Section: Binge-eating Experimental Proceduresmentioning
confidence: 57%
“…Indeed, stress‐related disorders are positively correlated with bingeing episodes and are more prevalent in females, underscoring the importance of designing ethologically relevant animal models to investigate the interplay between stress and bingeing behaviors . In 2009 Cifani et al reported an elegant model of emotional stress‐induced binge eating in female rats where repeated cyclic caloric restriction induced binge eating of highly palatable food when exposed to a frustrative stressor . This protocol models the impact of “yo yo dieting” on binge eating behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] In 2009 Cifani et al reported an elegant model of emotional stress-induced binge eating in female rats where repeated cyclic caloric restriction induced binge eating of highly palatable food when exposed to a frustrative stressor. 5,7,16,17 This protocol models the impact of "yo yo dieting" on binge eating behavior. We wanted to extend these findings to establish whether this behavior can be observed in the absence of a history of caloric restriction and could be readily modeled in mice.…”
Section: Introductionmentioning
confidence: 99%